The Effectiveness of Hot Fomentation with Epsom Salt Versus Common Salt on Knee Joint Pain among Elderly in the Selected Old Age Home of Pune City - Derin Okram1 , Dipak Sethi2 , Ranjana Chavan3 , Sharadha Ramesh4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background & Objective: Aging is a multidimensional process of change in the physical, psychologicaland social. In India Osteoarthritis 2nd most cause of knee joint pain with the prevalence of 22 to 39%. Ouraim was to assess the effectiveness of hot fomentation with Epsom salt versus Common salt on knee jointpain among elderlyMethods: A Quasi Experimental, Non- randomized one group pre-test post-test control group design wasadopted involving 40 elderly who have knee joint pain. After obtaining informed consent elderly wereallocated into two groups of 20 each by using the Non-probability purposive sampling technique. Hotfomentation (100 ml of water at the temperature of 30-40 degree Celsius) with 2gm of Epsom salt for theexperimental group and common salt for the attention control group for 5 days once a day. Global pain scalewas used to assess the level of pain.Results: The significant change was observed in Pain level as evident that the t-value is 26.29, p-value ofEpsom is 0.00001 that is less than 0.05 and the t-value is -21.03, p-value of Common salt is 0.0001 that isless than 0.05, both the interventions were effective but Epsom salt is more effective than common salt onknee joint pain. Hence, null hypothesis (H0) was rejected. None of the demographic variables are found tohave significant association with the level of knee joint pain.Conclusion: The effectiveness of hot fomentation with Epsom salt is higher than the common salt so nullhypothesis is rejected.